2013
DOI: 10.2341/11-325-l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resin-Modified Glass Ionomer Containing Bioactive Glass on the Flexural Strength and Morphology of Demineralized Dentin

Abstract: Flexural strength of the human dentin decreases after it is demineralized in vitro. This in vitro study demonstrates that resin-modified glass ionomer (RMGI) containing bioactive glass (BAG) can compensate for this loss of strength. RMGI without BAG does not restore the strength of such demineralized dentin. SUMMARYIntroduction: Recently, bioactive materials have been incorporated into glass ionomer cements to promote the precipitation of calcium phosphates in surrounding tooth structures. This in vitro study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 39 publications
0
23
0
3
Order By: Relevance
“…It was also reported that incorporation of a large amount of HA (50 to 60 wt%) into light-cured monomer could increase Young’s modulus and surface hardness and this large amount of HA was used as the only reinforcing filler in that study (22). However, in the present study, smaller volumes of HA (5,15 and 25 wt%) were added to glass powder similar to previous studies (2,3). Geonka et al synthesized the nanocrystalline calcium-deficient HA into GIC in different compositions (5, 10 and 15 wt%) and reported that the group containing 5% HA had higher surface microhardness than the 15% HA-GIC group.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…It was also reported that incorporation of a large amount of HA (50 to 60 wt%) into light-cured monomer could increase Young’s modulus and surface hardness and this large amount of HA was used as the only reinforcing filler in that study (22). However, in the present study, smaller volumes of HA (5,15 and 25 wt%) were added to glass powder similar to previous studies (2,3). Geonka et al synthesized the nanocrystalline calcium-deficient HA into GIC in different compositions (5, 10 and 15 wt%) and reported that the group containing 5% HA had higher surface microhardness than the 15% HA-GIC group.…”
Section: Discussionmentioning
confidence: 81%
“…Glass-ionomer cements (GICs) are used in clinical dentistry as commercial materials since the early 1970s (1,2). The success of these cements is attributed to their unique properties such as direct bonding to tooth structure, anti-cariogenic action due to release of fluoride and biocompatibility with pulp tissue (3,4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it possesses a remineralization effect on the demineralized tooth structure by releasing calcium and phosphate ions, as well as antibacterial and acid neutralizing properties through the increase in pH by the release of alkali ions during dissolution of BAG in an aqueous environment [9,10,11]. In this regard, in dentistry, BAGs have been studied for the augmentation of alveolar ridges, the treatment of periodontal pocket, a filler component of dental materials, such as restorative materials, cements, pit and fissure sealants, and also for the treatment of hypersensitive teeth [12,13,14,15]. …”
Section: Introductionmentioning
confidence: 99%
“…Glass ionomer cements (GICs) (also referred to as polyalkanoate cements or aluminosilicate-polyacrylic acid cements), glassy powder based on acid soluble calcium fluoroaluminosilicate and polyacrylic acids with copolymers in liquid form used for dental fillings and luting cements, capable of stabilizing teeth calcium-deficient carbonated HA by ion exchange [50]: the carboxylic groups of GICs replace the phosphate ions of the teeth HA surface to establish ionic bonds with calcium ions derived from the partially dissolved crystals [51]. GICs interfere with subgingival biofilm formation, decreasing the irritation of the periodontal tissues [52].…”
Section: Restorative Approaches To Pathological Alterationsmentioning
confidence: 99%